2018
DOI: 10.7150/thno.21099
|View full text |Cite
|
Sign up to set email alerts
|

Parametric optimization of electric field strength for cancer electrochemotherapy on a chip-based model

Abstract: Electrochemotherapy (ECT), as one of the very few available treatments for cutaneous and subcutaneous tumors when surgery and radiotherapy are no longer available, requires applying a proper electric field to the tumor to realize electroporation-mediated cytotoxic drug delivery. It is impossible to exhaust all possible electrical parameters on patients to realize the optimal tradeoff between tumor suppression and adverse effects. To address this issue, this study provides a feasible solution by developing a fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…On the other hand, animal models for drug testing are labor/time intensive, costly, and most importantly, often yield untranslatable results due to the physiological differences between humans and animal models 11-14. Therefore, the creation of cost-effective, reliable, and pragmatic in vitro models that can be used for accurately screening anticancer drug effects as well as overcoming the drawbacks of conventional models is of great importance for improving the current clinical management of primary tumor and metastatic cancer 15-18.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, animal models for drug testing are labor/time intensive, costly, and most importantly, often yield untranslatable results due to the physiological differences between humans and animal models 11-14. Therefore, the creation of cost-effective, reliable, and pragmatic in vitro models that can be used for accurately screening anticancer drug effects as well as overcoming the drawbacks of conventional models is of great importance for improving the current clinical management of primary tumor and metastatic cancer 15-18.…”
Section: Introductionmentioning
confidence: 99%
“…In spite of the extensive clinical application of cisplatin, the side effects and resistance of patients towards this drug have promoted the development of novel combination therapy 11,12 . Amongst, electrochemotherapy 12–15 is a novel therapeutical strategy for the treatment of solid tumors by exposing the cells to electric fields to improve the bioactivity of non‐permeable or low permeable anticancer drugs, such as cisplatin. It is reported that the introduction of electric fields can effectively enhance the cytotoxicity of cisplatin via increasing the cell membrane permeability to this drug 16,17 .…”
Section: Introductionmentioning
confidence: 99%
“…Electrochemotherapy (ECT) [25][26][27] is an effective treatment strategy of solid tumors by exposing tumor issue under pulse electric fields to enhance the anticancer activity of specific drugs. Previous studies have revealed that electrochemotherapy can selectively kill tumor cells to avoid harming the surrounding normal tissue, [28] and has been approved to be used in clinical practice.…”
Section: Introductionmentioning
confidence: 99%